BAKODEK JO NAN SINGKEK - Arif Kurnia Putra; Wimbrayardi Wimbrayardi; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2014)
Abstract This piece of music was created as the response to the phenomena of moral and ethics change of Minangkabau people through voice media. This was done by considering the concept of producing rhythm and melody which were expressed in several expression media wich then interpreted the meaning of Bakodek Jo nan Singkek. Technically, the media or instruments used were combined with the others so that the atmosphere needed was in line to work concept. Kata Kunci: Karya Seni, Bakodek, Singkek, Minangkabau